1992
DOI: 10.1002/jmri.1880020104
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of nonionic low‐osmolar gadodiamide injection in animals with intracranial mass lesions

Abstract: Gadodiamide injection is a nonionic, low-osmolar formulation of a paramagnetic metal chelate complex consisting of gadodiamide and caldiamide sodium. The efficacy of gadodiamide injection as a magnetic resonance (MR) imaging enhancement medium was evaluated by imaging intracranial 9L-glioma lesions induced in rats and naturally occurring lesions in dogs. T1- and T2-weighted spin-echo images were obtained before and after administration of gadodiamide injection at doses of 0.1 and 0.2 mmol/kg. On the precontras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In contrast, the BBB is not an issue for in vivo tracer uptake by 9L gliosarcoma cells as intracranially implanted 9L tumors do not have a functional BBB as demonstrated by gadolinium-enhanced magnetic resonance imaging studies. 37,38 However, the differences in the biologic behaviors of the ( R )- and ( S )-enantiomers in the cell uptake assays and the in vivo biodistribution studies provide strong evidence that the high tumor to brain ratios observed with ( S )-[ 18 F] 4 are not due to passive BBB effects alone. Failure to cross the normal BBB may limit the role of ( S )-[ 18 F] 4 for imaging gliomas with relatively intact BBBs, in particular low-grade gliomas.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the BBB is not an issue for in vivo tracer uptake by 9L gliosarcoma cells as intracranially implanted 9L tumors do not have a functional BBB as demonstrated by gadolinium-enhanced magnetic resonance imaging studies. 37,38 However, the differences in the biologic behaviors of the ( R )- and ( S )-enantiomers in the cell uptake assays and the in vivo biodistribution studies provide strong evidence that the high tumor to brain ratios observed with ( S )-[ 18 F] 4 are not due to passive BBB effects alone. Failure to cross the normal BBB may limit the role of ( S )-[ 18 F] 4 for imaging gliomas with relatively intact BBBs, in particular low-grade gliomas.…”
Section: Resultsmentioning
confidence: 99%